Pengaruh Senam Anak Indonesia Hebat Terhadap Peningkatan Kebugaran Jasmani Siswa Kelas V Di SDN Pasir Benteng II - Akbar Ramdani; Dinar Dinangsit; Encep Sudirjo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to evaluate the effectiveness of the Senam Anak Indonesia Hebat (SAIH) program in improving the physical fitness of fifth-grade students at SDN Pasirbenteng II. The research method used was a quantitative quasi-experimental design with a one-group pretest-posttest on 34 students selected through purposive sampling. Data were collected using the Indonesian Student Fitness Test (TKSI) package and analyzed using a paired t-test and the coefficient of determination (R2) test. Scientific findings showed a significant increase in all fitness variables (p < 0.05). The R2 test result of 0.796 proved that SAIH contributed 79.6% to improving student fitness. The conclusion of this study is that SAIH is a very effective and measurable physical exercise instrument to improve the physical quality of students in elementary schools. Keywords: Physical fitness, great indonesian children’s gymnastics.